Intraspecific divergence and DNA barcodes in Systrophia helicycloides (Gastropoda, Scolodontidae) - Romero, Pedro (2011)
DNA barcoding analysis is based on the comparison of genetic distances to identify species using a segment of Cytochrome C Oxidase I (COI) gene. Species identification through DNA barcoding challenges problems in groups with high genetic diversity as molluscs. Thus, our aim was to estimate intraspecific divergence in the Amazonian land snail Systrophia helicycloides (Gastropoda, Scolodontidae) and evaluate the use of DNA barcoding in molecular identification of this land snail. Nucleotide sequences were compared with Genbank and BOLD (Barcode of Life Data Systems) databases. We conducted distance analyses using the Neighbour Joining method. Systrophia helicycloides showed two groups of haplotypes and intraspecific genetic distances higher than 4%. We observed an overlap between intraspecific and interspecific distances. The high divergence may be related to rapid mutation rate in the snail mitochondrial genome, to population distribution that influences genetic isolation and differentiation, and to ancestral DNA polymorphisms. COI profiles uploaded in BOLD are the first records of this species and can identify Systrophia helcycloides from other species. These profiles corroborated the high variation in the land snail genome. Therefore, species identification in this group needs a combined analysis of genetic distances, informative sites, and conventional taxonomy.